A review of sustainable biofuels from waste materials: development and challenges - Washima, Antara; Raka, Tarannum; Fazrin, Mariha (Brac University, 2022)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Microbiology, 2021.